Judgment and salvation: a rhetorical-critical reading of Noah's flood in Genesis - Burlet, Dustin G. (Pickwick Publications, 2022)
"This book contends the text of the Noachian deluge narrative categorically underscores all God did to preserve life in spite of the disaster. Despite the picture of devastation that the narrative depicts, the prominent emphasis of the text is on deliverance and redemption, i.e., salvation, not judgment. The focus of the Genesis flood is acutely bent towards God's salvific rather than punitive purposes. The arc of salvation within the flood narrative can be broken down into two main ideas. Firstly, God's intention for creation is not thwarted, and, secondly, God commits himself to his intentions of creation. God's intention for creation can be stated thus: the establishment of order via covenant showing the sanctity of human life and the upholding of all life. This involves, in particular, humanity as his image bearers, including the lex talionis (life-for-life) principle." --